A silicon-rhodamine chemical-genetic hybrid for far red voltage imaging from defined neurons in brain slice. Issue 6 (5th October 2021) - Ortiz, Gloria; Liu, Pei; Deal, Parker E.; Nensel, Ashley K.; Martinez, Kayli N.; Shamardani, Kiarash; Adesnik, Hillel; Miller, Evan W.
Abstract : Small-molecule enzyme hybrids pair a far-red voltage-sensitive fluorophore with a cell-surface expressed HaloTag enzyme via a flexible linker to enable voltage imaging from genetically defined neurons in culture and brain slice. Abstract : We describe the design, synthesis, and application of voltage-sensitive silicon rhodamines. Based on the Berkeley Red Sensor of Transmembrane potential, or BeRST, scaffold, the new dyes possess an isomeric molecular wire for improved alignment in the plasma membrane and 2′ carboxylic acids for ready functionalization. The new isoBeRST dyes have a voltage sensitivity of 24% Δ F / F per 100 mV. Combined with a flexible polyethyleneglycol (PEG) linker and a chloroalkane HaloTag ligand, isoBeRST dyes enable voltage imaging from genetically defined cells and neurons and provide improved labeling over previous, rhodamine-based hybrid strategies. isoBeRST-Halo hybrid indicators achieve single-trial voltage imaging of membrane potential dynamics from cultured hippocampal neurons or cortical neurons in brain slices. With far-red/near infrared excitation and emission, turn-on response to action potentials, and effective cell labeling in thick tissue, the new isoBeRST-Halo derivatives provide an important complement to voltage imaging in neurobiology.